Assessment of mouth opening limitation in myogenic temporomandibular disorder patients - Ahmed A Al-Tuhafi (University of Mosul, College of Dentistry, 2005)
Abstract This research was to evaluate a new assessment of mouth opening limitation in myogenic temporomandibular disorder (TMD) patients. The suggested assessment was accomplished by calculating the opening ratio (OR) which depends on the ratio between maximum comfortable mouth opening and maximum assisted mouth opening. There was a remarked significant difference in the OR between the TMD patients and control groups. There was no significant relationship between OR with age or sex in both groups. A significant reversible correlation between OR with number of tender muscles and temporomandibular joint tenderness was found. It could be concluded from this research that the OR has diagnostic value in TMD patients, but unlike other measures, as it independent on age and gender.